Changes in Resting Salivary Testosterone, Cortisol and Interleukin-6 as Biomarkers of Overtraining (Baltic Journal of Sport and Health Sciences, 2016)
Background.  Overtraining  (OVT)  is  a  concern  for  many  athletes.  Immunological  (increased  interleukin-6  [IL-6]) and hormonal (increased cortisol [C], decreased free testosterone [fT]) biomarkers have been analyzed during training to detect OVT development. Methods. This study determined if resting levels of salivary IL-6, T, and C change during a pre-season resistance training (RT) program in 20 Division I American football players (mean ± SD: age = 19.1 ± 1.1 years; height = 185.4 ± 6.7 cm; mass = 102.0 ± 22.2 kg; body fat = 14.7 ± 7.6%). 1RM squat, bench press and Olympic-style clean, IL-6, C and T were assessed at baseline (WK1), week 4 (WK4), week 6 (WK6) along with psychological status (PS) to determine affective state. Results. 1RM (bench press: 121.6 ± 36.3 kg vs. 127.4 ± 35.9 kg, squat: 187.2 ± 30.2 kg, 190.9 ± 28.1 kg, clean: 116.8 ± 14.6 kg, vs. 119.2 ± 14.5 kg), IL-6 (1.42 ± 1.77 pg/mL vs. 5.60 ± 12.57 pg/mL) and C (2.57 ±  2.46 nmol/L vs. 5.33 ± 4.94) increased significantly from WK1 to WK6 ( p < .05), fT decreased significantly (417.44 ± 83.63 pmol/L vs. 341.10 ± 87.79 pmol/L) from WK1 to WK6 (p < .05). PS was minimally affected during the study. Significant biomarker changes were detected, but no OVT was induced (i.e. performance improved).Conclusion. Therefore, directional changes in these biomarkers may not be sufficiently reflective of OVT in RT programs.Keywords: stress, hormones, biomarkers, anabolic-catabolic